2015
DOI: 10.1111/cdev.12380
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Faces Expressing Negative Emotion at 7 Months Predicts Attachment Security at 14 Months

Abstract: To investigate potential infant‐related antecedents characterizing later attachment security, this study tested whether attention to facial expressions, assessed with an eye‐tracking paradigm at 7 months of age (N = 73), predicted infant–mother attachment in the Strange Situation Procedure at 14 months. Attention to fearful faces at 7 months predicted attachment security, with a smaller attentional bias to fearful expressions associated with insecure attachment. Attachment disorganization in particular was lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
115
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(127 citation statements)
references
References 79 publications
11
115
1
Order By: Relevance
“…Given that the test task performance was technically successful and very comparative with many previous studies [40,43], the lack of differences cannot be attributed to methodological issues in test administration. Furthermore, earlier work has shown that the eye-tracking-based method is sensitive enough to measure clinically subtle effects such as single nucleotide gene polymorphisms or preterm birth; both were shown to affect eye-tracking-based measures [62][63][64].…”
Section: Visual Orienting Of Attentionmentioning
confidence: 83%
See 4 more Smart Citations
“…Given that the test task performance was technically successful and very comparative with many previous studies [40,43], the lack of differences cannot be attributed to methodological issues in test administration. Furthermore, earlier work has shown that the eye-tracking-based method is sensitive enough to measure clinically subtle effects such as single nucleotide gene polymorphisms or preterm birth; both were shown to affect eye-tracking-based measures [62][63][64].…”
Section: Visual Orienting Of Attentionmentioning
confidence: 83%
“…The eye-tracking test was designed to assess infants' attention to nonface patterns and faces by using a face-distractor competition paradigm [31,40]. In this paradigm, infants fixate a nonface pattern or a picture of a face in the center of the screen while a lateral distractor stimulus (geometric shape) is presented to the left or to the right.…”
Section: Eye-trackermentioning
confidence: 99%
See 3 more Smart Citations